Application of Artificial Intelligence in the Intervention of Sports on Adolescent Health Risk Behavior - Jin Ha (Applied Bionics and Biomechanics)
Through school education to intervene in the behavior of adolescent health risk behaviors students and guide students to have a correct concept of quality and health, this paper uses artificial intelligence technology to mine students’ body language to analyze students’ behavior in quality education dance classes, so as to achieve effective intervention for AHRB students. Before the experimental study, AHRB students and normal students were mixed into groups in a ratio of not less than 1 : 18. The results of the study showed that the implementation of intervention strategies could reduce the recurrence of various risky behaviors in adolescents. When non-AHRB students and AHRB students intervene together, there will be no adverse effects on non-AHRB students.